The relationship between rural credit and member loyalty in a credit cooperative in the municipality of Rondinha, RS, Southern Brazil - Tiago Cazzaroto; Tadeu Grando; Débora Gomes de Gomes; Suelen Corrêa (Revista Ambiente Contábil, 2025)
Objective: The study aims to verify the relationship between rural credit and member loyalty in a credit cooperative in Rondinha, RS, Southern Brazil.